Regulation of CD4+ T Cell Signaling and Immunological Synapse by Protein Tyrosine Phosphatases: Molecular Mechanisms in Autoimmunity - Castro-Sánchez, Patricia; Aguilar-Sopeña, Oscar; Alegre-Gómez, Sergio; Ramirez-Munoz, Rocio; Roda-Navarro, Pedro (Frontiers in Immunology, 2019)
T cell activation and effector function is mediated by the formation of a long-lasting interaction established between T cells and antigen-presenting cells called immunological synapse (IS). During T cell activation, different signaling molecules as well as the cytoskeleton and the endosomal compartment are polarized to the IS. This molecular dynamics is tightly regulated by phosphorylation networks, which are controlled by protein tyrosine phosphatases (PTPs). While some PTPs are known to be important regulators of adhesion, ligand discrimination or the stimulation threshold, there is still little information about the regulatory role of PTPs in cytoskeleton rearrangements and endosomal compartment dynamics. Besides, spatial and temporal regulation of PTPs and substrates at the IS is only barely known. Consistent with an important role of PTPs in T cell activation, multiple mutations as well as altered expression levels or dynamic behaviors have been associated with autoimmune diseases. However, the precise mechanism for the regulation of T cell activation and effector function by PTPs in health and autoimmunity is not fully understood. Herein, we review the current knowledge about the regulatory role of PTPs in CD4+ T cell activation, IS assembly and effector function. The potential molecular mechanisms mediating the action of these enzymes in autoimmune disorders are discussed.